Fruit trees and herbaceous plants increase functional and phylogenetic diversity of birds in smallholder rubber plantations. (May 2021) - Jayathilake, H. Manjari; Warren-Thomas, Eleanor; Nelson, Luke; Dolman, Paul; Bumrungsri, Sara; Juthong, Watinee; Carrasco, L. Roman; Edwards, David P.
Abstract: Rubber plantations are widespread in mainland South-east Asia. Intensive monocultural rubber cultivation practices predominate, which negatively impact biodiversity. Some plantations are managed as high-yielding agroforests, where the integration of fruit trees and other plant species marginally enhances crop diversity relative to monocultures, providing benefits for species richness of some taxa without compromising yields. A key question is whether these high-yielding agroforestry systems also support enhanced functional and phylogenetic diversity relative to monoculture. Focusing on birds in rubber monocultures and agroforests in two provinces of Southern Thailand, we study plantation habitat structure and wider landscape characteristics to identify effects on functional and phylogenetic diversity metrics. Functional diversity, phylogenetic diversity and evolutionary distinctiveness of birds were comparable between rubber monocultures and intensive agroforests. The density of fruit stems and taller herbaceous plants within agroforests positively influenced functional and phylogenetic diversity, and evolutionary distinctiveness. Functional and phylogenetic diversity was higher in landscapes with a greater proportion of fruit orchards, but was lower in landscapes with a greater proportion of degraded natural forest patches. Our study suggests that the integration of fruit trees and maintaining taller herbaceous plants within rubber plantations could help support bird diversity at evolutionary and functional levels. Small patches of degraded forest in areas dominated by agriculture may need time to generate positive spillover effects on the functional and phylogenetic diversity of birds within rubber plantations. Better management of existing rubber plantations could sustain higher diversity, while offering food security and alternative revenue streams.